(untitled) (Journal of Music Research Online, 2022)
In this paper I aim to introduce the piano-accompanied songs of Dutch-Australian composer Meta Overman to scholars and performers. A brief biographical survey sketches her musical training in Rotterdam, especially under important composer-teacher Willem Pijper, and then a short survey of major Dutch song composers of the preceding two generations sets her songwriting in context. I will argue that the music of Willem Pijper and Alphonse Diepenbrock influenced her compositional technique and I point out affinities with other song composers, notably Matthijs Vermeulen, Henri Zagwijn and Henriëtte Bosmans. All of her songs are examined critically, with straightforward harmonic analysis. It is helpful to divide her song output (twenty-three in total) into two loose groups: those written before 1932 as she searched for her individual voice and those after she emigrated to Australia in 1947 and achieved her mature powers. Her best work is in settings of short suggestive lyrics where she captures the music of the words in a sensitive lyricism with colourful piano parts tied closely to the text.